Green Tourism Policy: Studi Komparatif Kebijakan Pariwisata Berkelanjutan di Indonesia dan Malaysia - Adang Aldhila (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2025)
This study analyzes the comparative green tourism policies of Indonesia and Malaysia from a comparative public administration perspective. The effectiveness of sustainable tourism is determined not only by the substance of the policy but also by the institutional structure and governance capacity of the country. The study uses a qualitative approach with a comparative public policy design. The results show that Indonesia implements a decentralized participatory green governance model that emphasizes community empowerment and regional flexibility, but faces the challenge of fragmented implementation due to variations in institutional capacity. In contrast, Malaysia has developed a centralized regulatory green governance model that is more consistent in standardizing and overseeing policies through strong federal coordination. Differences in state administrative structures have been shown to be a determining factor in the design and effectiveness of sustainable tourism policies. This study confirms that strengthening green tourism requires a balance between national regulatory consistency and local participation as the foundation of sustainable governance.